BASIC COMPUTER NETWORKING TRAINER: HOW DOES THE EFFECTIVENESS TOWARDS LEARNING OUTCOMES IMPROVEMENTS? - Khrisna Bagaskara; Agus Efendi; Puspanda Hatta (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2019)
Learning media like simulator application was used in many learning processes at education institutes such as school and university. Based on observation, practicing using real equipment such as trainer media more effective than using the simulator as learning media to improving students comprehension in the learning process. On the previous work, Basic Computer Networking Trainer was developed that aims to improve students learning outcomes. This study aims to find out: The effectiveness of Basic Computer Networking Trainer towards learning outcomes at Computer Networking 1 subjects. This study using the experimental method with Quasi-Experimental Design. This study was done within 2 groups divided into experiment group treated using Basic Computer Networking Trainer and control group treated using Cisco Packet Tracer. Both groups were given by writing test. First was pre-test that given before treatment and post-test given after treatment. The sample of this study was 42 students 2nd grades of Information Technology and Computer Education, Teacher Training and Education Faculty of Sebelas Maret University, Surakarta.Keywords: effectiveness, basic computer networking trainer, learning outcomes